2011
DOI: 10.1029/2010wr010229
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between specific surface area and the dry end of the water retention curve for soils with varying clay and organic carbon contents

Abstract: Accurate description of the soil water retention curve (SWRC) at low water contents is important for simulating water dynamics and biochemical vadose zone processes in arid environments. Soil water retention data corresponding to matric potentials of less than −10 MPa, where adsorptive forces dominate over capillary forces, have also been used to estimate soil specific surface area (SA). In the present study, the dry end of the SWRC was measured with a chilled‐mirror dew point psychrometer for 41 Danish soils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 51 publications
7
85
1
Order By: Relevance
“…Th erefore, we hypothesize that soil hygroscopic water content, whose determination is fast and technically less involved than particle-size analysis, positively correlates with clay percentage in both temperate and tropical soils and can provide a useful surrogate for soil clay content. Other research groups have presented results that emphasize the strong correlation between hygroscopic water and clay contents (Banin and Amiel, 1970;Petersen et al, 1996;Tuller and Or, 2005;Resurreccion et al, 2011); however, there is no specifi c water potential or relative humidity (RH) agreed on at which these relationships should be determined.…”
Section: Laëtitia Bréchetmentioning
confidence: 99%
“…Th erefore, we hypothesize that soil hygroscopic water content, whose determination is fast and technically less involved than particle-size analysis, positively correlates with clay percentage in both temperate and tropical soils and can provide a useful surrogate for soil clay content. Other research groups have presented results that emphasize the strong correlation between hygroscopic water and clay contents (Banin and Amiel, 1970;Petersen et al, 1996;Tuller and Or, 2005;Resurreccion et al, 2011); however, there is no specifi c water potential or relative humidity (RH) agreed on at which these relationships should be determined.…”
Section: Laëtitia Bréchetmentioning
confidence: 99%
“…[17] Although the Langmuir model was derived for low ionic strength solutions, the exponential form between film thickness f REV (or water content ) and matric potential h REV (4/ << h REV at low water contents) of different soils were proved to be reliable not only in other SWRC models that account for film flow (e.g., the (h) model introduced by Tuller and Or [2005]), but also in laboratory experiments (e.g., the measured h(f) of different soils at very dry ranges in Resurreccion et al [2011]). …”
Section: H() and K(h) Accounting For Film Flowmentioning
confidence: 99%
“…The details of our experiment were the same as those of Resurreccion et al [2011]. First, air-dried samples of 10 g were prepared and a small amount of water was added.…”
Section: Experimental Methods 221 Measured (H) Of Very Dry Samplesmentioning
confidence: 99%
“…Previous work showed that the S SA of soil is closely dependent upon the soil texture and that it could be estimated from the 5 soil media data and PSD (Sepaskhah and Tafteh, 2013;Resurreccion et al, 2015). The method used to estimate the S SA in Sect.…”
Section: The Effects Of Estimated S Sa Valuesmentioning
confidence: 99%